VD_FINDINFO Jug / 2016 / 231 vom 2. Dezember 2015 - VD Tribunal cantonal (2015)
PRÉSOMPTION D'INNOCENCE, INDEMNITÉEN GÉNÉRAL, DOMMAGE INDIRECT, TORT MORAL | 47 CO, 49 CO, 180 al. 1 CP, 10 CPP (CH), 115 al. 1 CPP (CH), 433 al. 1 CPP(CH)